ANALISIS KESALAHAN SISWA BERBAKAT MATEMATIKA DALAM MEMECAHKAN MASALAH TRANSFORMASI GEOMETRI BERDASARKAN LANGKAH POLYA - Leady Dione Alfa Giovanni; I Nengah Parta; Hery Susanto; Lathiful Anwar (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
This research is motivated by the importance of knowing the errors of gifted math students in solving geometric problems, so that the coaching teacher will find it easier to find solutions and the student's mastery of the material can increase. The purpose of this research is to describe types of errors and the factors causing gifted math students in solving geometry transformation problem. Data collection method was done by conducting a test about geometry transformation problem and by conducting an interview. The results of this research were the type of error done by gifted math students covering a mistake in doing solving plan and rechecking the answer. Most error done by them were in rechecking their answer, that was they had misconception in geometry transformation and they made an error in deciding a formed rectangle type. Factor causing the error in doing solving plan was they were careless in constructing the process of problem solving based on known information. Besides, they were also rarely writing unit in each problem. Factor causing error in rechecking step was the students did not make a correction based on information that they asked and also time limitation in rechecking the answer they had got.